IMPLEMENTASI PENILAIAN KOMPETENSI BERBICARA MATA KULIAH BAHASA INDONESIA - Laila Fitri Nur Hidayah; Sarwiji Suwandi; Sumarwati Sumarwati (Kantor Bahasa Provinsi Maluku Utara, 2021)
The inaccuracy in the assessment results in the difficulty of students expressing themselves in spoken language. The purpose of this research is related to the context, this study examines the condition of the characteristics of students, educators, and the campus environment, as a support for the implementation of the speaking competency assessment. Input, relating to materials and facilities developed to support the implementation of speaking competency assessment. Process, related to the implementation of the speaking competency assessment. The product, the quantity of the achievement of the assessment objectives, the quality of the achievement of the assessment objectives, and the benefits of the achievement of the assessment objectives, from the implementation of the speaking competency assessment at Higher Education. Judging from the type, This study is included in the CIPP evaluation study. The data in this study are qualitative. The data in this study are in the form of googleform, syllabus, RPS, interviews, and the results of standard agreements in focus group discussions and observations of the learning process. This research involved three lecturers each from three Islamic universities in Surakarta, 479 students, and 14 study programs. The results of this study indicate that in the context implementation, input, process, product, and assessment have not fully met the standards set by the government in Permendikbud Number 3 of 2020. Learning to speak Indonesian subjects is based on HOTS although there are several aspects of the assessment that are still LOTS.